Transcriptomic and proteomic analyses of Mangifera indica in response to Xanthomonas critis pv. mangiferaeindicae - Liu, Feng; Sun, Xin; Wang, Lulu; Zhou, Kaibing; Yao, Quansheng; Zhan, Ru-lin (Frontiers in Microbiology, 2023)
Mango is an important tropical fruit with the reputation of "Tropical Fruit King." It is widely cultivated in tropical and subtropical regions. Mango bacterial leaf spot, which is caused by Xanthomonas critis pv. mangiferaeindicae (Xcm), poses a great threat to the development of mango planting industry. In this study, we used RNA sequencing and data-independent acquisition techniques to compare the transcriptome and proteome of the highly resistant cultivar "Renong No.1" (RN) and the highly susceptible cultivar "Keitt" (KT) in response to Xcm infection at different stages (0, 2, and 6 days). A total of 14,397 differentially expressed genes (DEGs) were identified in the transcriptome of the two varieties, and 4,400 and 8,926 genes were differentially expressed in RN and KT, respectively. Among them, 217 DEGs were related to plant hormone signaling pathway, and 202 were involved in the maintenance of cellular redox homeostasis. A total of 3,438 differentially expressed proteins (DEPs) were identified in the proteome of the two varieties. Exactly 1,542 and 1,700 DEPs were detected in RN and KT, respectively. In addition, 39 DEPs were related to plant hormone signaling pathway, whereas 68 were involved in the maintenance of cellular redox homeostasis. Through cross-validation of the two omics, 1,470 genes were found to be expressed in both groups, and a large number of glutathione metabolism-related genes, such as HSP26-A, G6PD4, and GPX2, were up-regulated in both omics. Peroxisome-related genes, such as LACS6, LACS9, PED1, GLO4, and HACL, were up-regulated or down-regulated in both omics. ABCB11, SAPK2, MYC2, TAG7, PYL1, and other genes related to indole-3-acetic acid and abscisic acid signal transduction and plant-pathogen interaction were up-regulated or down-regulated in both omics. We also used weighted gene co-expression network analysis to combine physiological and biochemical data (superoxide dismutase and catalase activity changes) with transcriptome and proteome data and finally identified three hub genes/proteins (SAG113, SRK2A, and ABCB1) that play an important role in plant hormone signal transduction. This work was the first study of gene/protein changes in resistant and susceptible mango varieties, and its results improved our understanding of the molecular mechanism of mango resistance to Xcm.